Set of connectors for enterprise information system architecture - Bagušytė, Lina; Lupeikienė, Audronė (Lietuvos matematikos rinkinys, 2009)
This paper analyses enterprise information system (EIS) design problem. It is showed that current design methodologies do not provide adequate support for the development of EIS. The problem classes solved by modern EIS and their peculiarities are presented. Architectural styles and their merging possibilities are analysed. The set of connectors for enterprise information system architecture is proposed.
Keywords: information system architecture; architecture style; connector